Distinct ion irradiation response in VTaTi medium entropy alloy from elemental metal V. (15th January 2023) - Mei, L.; Zhang, Q.; Dou, Y.; Fu, E.G.; Li, L.; Chen, S.; Dong, Y.; Guo, X.; He, X.; Yang, W.; Xue, Y.; Jin, K.
Abstract: The microstructural and mechanical property changes induced by 6 MeV titanium ion irradiation are comparatively investigated between a refractory medium-entropy alloy VTaTi and elemental metal V. Compared with V, the aggregation of irradiation induced defect clusters in VTaTi is strongly suppressed, as evidenced by the much smaller defect size. Moreover, the loops in VTaTi are dominantly <100>-type, in contrast to those in elemental metal V being mainly 1/2<111>-type. Furthermore, nanoindentation tests show that the irradiation hardening in VTaTi is significantly weaker than V, further demonstrating its improved irradiation resistance. Graphical abstract: Image, graphical abstract